ANALISIS SISTEM STANDARD MUTU AKADEMIK FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS BUDI LUHUR - Dwi Achadiani; Purwanto Purwanto; Nazir Harjanto (Universitas Budi Luhur, 2012)
The academic quality standar in higher education is very important, likewise in faculty of information technology, University of Budi Luhur with a good academic quality, lecture system and eligible human resource, will produce quality graduates. Factors that play a rule in the process in academic quality standard in faculty of information technology, University of Budi Luhur include : grade selection to enter University of Budi Luhur, Grade Point Achievement (GPA=IPK), the study period active in student organization on campus, waiting time to get a first job conformity the study program with the work which is currently obtained. The factor which is most significant is the grade in entering faculty of information technology, University of Budi Luhur which is effecting significantly to GPA. Therefore, Dean and other managers of Faculty of Information Technology, University of Budi Luhur are necessary to maintain the initial selection to prospective student. And, the other factors have not effect significantly. This shows that learning process being carried out by faculty of information technology, University of Budi Luhur include curriculum and resources play an active role in producing quality graduates.Keywords : Quality standard, Academic Process, Quantitative Descriptive.